2017
DOI: 10.1016/j.cgh.2017.02.032
|View full text |Cite
|
Sign up to set email alerts
|

Coping Skills Are Associated With Gastrointestinal Symptom Severity and Somatization in Patients With Irritable Bowel Syndrome

Abstract: In a cross-sectional study of patients with IBS in Sweden, we found associations of levels of coping resources with GI and extraintestinal symptom severity; these associations were mediated by levels of anxiety and depressive symptoms. Although confirmation in longitudinal studies is needed, this identifies coping as a potential psychological treatment target in IBS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 44 publications
1
28
1
1
Order By: Relevance
“…28 Taken together, these findings indicate that fearful anticipation of painful visceral stimuli, as well as the context in which it occurs, may modulate subsequent brain responses to delivery of these stimuli in sensory as well as affective regions, and that these processes may go awry in IBS patients. This fits with the clinical observation that GI-specific fear and anxiety levels, 31 as well as levels of coping resources, 78 are associated with IBS symptom severity and course.…”
Section: Influence Of Life Events Stress and Other Affective Statessupporting
confidence: 88%
“…28 Taken together, these findings indicate that fearful anticipation of painful visceral stimuli, as well as the context in which it occurs, may modulate subsequent brain responses to delivery of these stimuli in sensory as well as affective regions, and that these processes may go awry in IBS patients. This fits with the clinical observation that GI-specific fear and anxiety levels, 31 as well as levels of coping resources, 78 are associated with IBS symptom severity and course.…”
Section: Influence Of Life Events Stress and Other Affective Statessupporting
confidence: 88%
“…The information of studies related to depressive symptoms has been summarised in Table S3. Analysis of 47 articles indicated that the pooled prevalence of depressive symptoms was 28.8% (95% CI: 23.6‐34; I 2 = 99.1%) in 22 842 IBS patients (Figure ). Visual inspection of the funnel plot indicates some asymmetry (Figure S5).…”
Section: Resultsmentioning
confidence: 99%
“…Many patients with FAPDs have reduced quality of life and functioning . The reason for this is unclear but may be related to a high number of comorbidities (including gastrointestinal, extra‐intestinal, and psychological) in addition to reduced coping skills . Despite evolving knowledge of aberrant brain‐gut signaling in patients with functional GI disorders, psychological disease is still often considered the only root of the problem.…”
Section: Discussionmentioning
confidence: 99%